Istima’ (Listening) Learning Strategy Used by Arabic Education Students - Moh Sholeh Afyuddin; M. Syamsul Ma’arif (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study aims to reveal the learning strategies that are reported more often used by Arabic language education students in studying maharah istima' and to elaborate on the practices to provide a comprehensive overview of how to learn istima'. This study is a mixed method with a sequential explanatory design, where the researcher takes quantitative data first, then explores it in more depth through qualitative data. The quantitative data taken through a questionnaire, adapted from O'Malley and Chamot, and Vandergrift's taxonomy of learning strategies, reported that cognitive learning strategies are used by 50.3%, metacognitive learning strategies are used by 39.1%, while socio-affective learning strategies are used by 44.5%. The qualitative data collected by follow-up interviews reported that the cognitive strategies used by students included inferencing, elaboration, imagery, translation, summarization, note-taking, and substitution. Inferencing, elaboration, imagery, and translation strategies are reported to be the most used, compared to summarization, note-taking, and substitution. Metacognitive strategies are reported to be used entirely, namely planning, monitoring, evaluation, and problem identification. Meanwhile, the socio-affective strategy was reported to be the least used of the three learning strategies and only used lowering anxiety, taking emotional temperature, and questioning for clarification.